FINANCIAL PERFORMANCE OF ISLAMIC BANKING IN NIGERIA: A CAMEL ANALYSIS OF JAIZ BANK PLC - Jimoh, Abdulrazaq T.; Attah, John A.; Abdul, Falilat A. (International Journal of Shari'ah and Corporate Governance Research, 2021)
Islamic banking started on a full-scale in Nigeria with the establishment of Jaiz bank which received its approval-in-principle from the Central Bank of Nigeria in 2011. As a non-interest bank, the bank has over the years, managed to compete with well-established conventional banks in the country in the area of financial intermediation. The question however is how the bank has been faring since its establishment in terms of financial performance. This study, therefore, assessed the performance of Jaiz Bank, for nine years from 2012 to 2020. Data were collected from Annual Reports of the Bank and financial ratio analysis was conducted within the framework of CAMEL. The study found that the bank performed averagely well in terms of capital adequacy, asset quality, earnings quality and liquidity during the period under consideration though with some managerial inefficiency. The conclusion was that the bank is in a good position to withstand an unexpected financial crisis. It was therefore recommended that the bank management should be more efficient in its financial intermediation function as this will solidify its position in the face of future uncertainties. JEL Classification Codes: G21, L25.